Photochemical reactivity of a binuclear Fe(I)–Fe(I) hydrogenase model compound with cyano ligands. (16th August 2016) - Hunt, Andrew; Barrett, Jacob; McCurry, Meghan; Works, Carmen
Graphical abstract: Iron–iron hydrogenase model compounds have potential as hydrogen producing catalysts that are inexpensive and environmentally friendly. Many of these model compounds are dependent on light for activity but little is know about the photochemical intermediates or products that are formed and catalytically important. The photochemistry of μ-pdt-[Fe(CO)2 CN]2 2− (2 ) is explored in acetonitrile and spectral changes in the IR support lost of CN−. UV–Vis spectroscopy was used to determine quantum yields for the disappearance of2, which was found to be 0.37 ± 0.04 in acetonitrile when irradiated with 365 nm light under nitrogen. Abstract: Iron–iron hydrogenase model compounds have potential as hydrogen producing catalysts that are inexpensive and environmentally friendly. Many of these model compounds are dependent on light for activity but little is know about the photochemical intermediates or products that are formed and catalytically important. The photochemistry of μ-pdt-[Fe(CO)2 CN]2 2− (2 ) is explored in acetonitrile and spectral changes in the IR support lost of CN−. UV–Vis spectroscopy was used to determine quantum yields for the disappearance of2, which was found to be 0.38 ± 0.04 in acetonitrile when irradiated with 365 nm light under nitrogen.